Company’s energy audit – supplementing the report with a summary information card - Kurtz-Orecka, Karolina (Instal, 2023)
The article presents the developed summary information card for the report on the energy audit of the company. The card allows for a significant extension of the scope of presented information, which is a synthesis of the report. The presented summation card can be used as a supplementary one to the official used card of the energy efficiency audit.
Keywords: company’s energy audit; audit card template; energy saving; energy efficiency; delivered energy